Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama

Das Unbehagen der Vermittler*innen – Was Grundschullehrer*innen über Holocaust-Bilderbücher für den Grundschulunterricht denken. Ergebnisse einer Interviewstudie zur Praxisakzeptanz literarästhetischer Holocaust-Begegnungen im Grundschulunterricht (Deutsch) - Kanning, Julian; Kruse, Iris; Inhoff, Julia (Deutschunterricht als Gedächtnisagentur. Didaktische Annäherungen an eine spezifische schulische Erinnerungskultur)

Analyzing student response processes to refine and validate a competency model and competency-based assessment task types - Soyka, Chantal; Schaper, Niclas (Frontiers in Education)

Bits und Bytes - Mikrocontroller verstehen mit modularer Hardware - Hetkämper, Tim; Meihost, Lars

Die (Ent-)Territorialisierung der Idylle. Zur produktiven Wechselseitigkeit surrealistischer Sehnsuchtsorte in bildender Kunst und Kinder- und Jugendmedien im Kontext der Studien visueller Kulturen - Böker, Ines (Idyllen und Sehnsuchtsorte in Literatur und Medien für Kinder und Jugendliche)

Evaluation and thermodynamic optimization of phase diagram of lithium niobate tantalate solid solutions - Bashir, Umar; Klimm, Detlef; Rüsing, Michael; Bickermann, Matthias; Ganschow, Steffen (Journal of Materials Science)
The lithium niobate–lithium tantalate solid solution’s phase diagram was investigated using experimental data from differential thermal analysis (DTA) and crystal growth. We used XRF analysis to determine the elemental composition of the crystals. The Neumann–Kopp rule provided essential data for the end members lithium niobate (LN) and lithium tantalate (LT). The heats of fusion of the end members, given by DTA measurements, are 103 kJ/mol at 1531 K for LN and 289 kJ/mol at 1913 K for LT. These values were used as input parameters to generate the data. This data served as the basis for calculating a phase diagram for LN-LT solid solutions. Finally, based on the experimental data and a thermodynamic solution model, the Calphad Factsage module optimized the phase diagram. We also generated thermodynamic parameters for Gibbs’ excess energy of the solid solution. A plot of the segregation coefficient as a function of Ta concentration was derived from the phase diagram.

Digitalisierungsbezogene Kompetenzen (angehender) Chemielehrkräfte - Ponath, Jonas; Bohrmann-Linde, Claudia; Rubner, Isabel; Sommer, Katrin; Fechner, Sabine (Frühe naturwissenschaftliche Bildung)

Ein Beitrag zur Steuerung der Faserstaubentwicklung faserverstärkter Kunststoffe beim mechanischen Recycling - Tölle, Lisa

Enhancing Relation Extraction Through Augmented Data: Large Language Models Unleashed - Manzoor, Ali; Sohail Nisar, Muhammad; Muhammad, Saleem; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (NLDB24)
Keywords: Nisar SFB-TRR Saleem climate_bOWL colide dice enexa kiam manzoor moussallem ngonga

Fever: Optimal Responsive View Synchronisation - Eranki, Varun Maitreya

Not your Average Digital Nudge: Heterogeneous Effects of Personalized Nudges with CausalML - Bösch, Kevin; Müller, Oliver; Weinmann, Markus (Proceedings of the Symposium on Statistical Challenges in Electronic Commerce Research)

Die Formierung katholischer Universitätstheologie im Königreich Preußen und der Hermesianismus - Ströhmer, Michael; Dahlke, Benjamin (Georg Hermes (1775-1831). Rationale Glaubensbegründung, theologische Konflikte und regionale Identitätsbildung im 19. Jahrhundert)

FSU als Bühne: Teatro aplicado - del Valle, Victoria (Fremdsprachendidaktik kurzgefasst)

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))
Augmented (AR) and Virtual Reality (VR) technologies have been applied very broadly in the recent past. While prior work emphasizes the potential of these technologies in various application domains, the process of visual attention in and across the contexts of AR/VR environments is not exhaustively explored yet. By now, visual attention in AR/VR environments has majorly been studied by means of overt attention (i.e. saccadic eye movements), self-report, and process-related visual attention proxies (like reaction time). In this work, we analyze covert visual attention based on the (psychological) Theory of Visual Attention (TVA), which allows us to quantify theory-based interpretable properties of the visual attention process. For example, the TVA allows us to measure the overall processing speed. We instantiate this TVA-based framework with a 30-participant explorative within-subjects study. The results show a decisive difference in visual attention between Reality (i.e. the neutral condition) and Virtual Reality and a weak difference between Reality and Augmented Reality. We discuss the consequences of our findings and provide ideas for future studies.
Keywords: Visual Attention; TVA; Cognitive Modelling; Bayesian Modelling; AR; VR

Totgeschwiegen. Die fehlende Stellungnahme zu Lage der Jüdinnen und Juden durch die Bekennende Kirche im Nationalsozialismus - Janus, Richard

Lehrpraktiken, Sozialisation und Selektion im Sozialraum Hochschule - Steinhardt, Isabel (Hochschullehre postdigital: Lehren und Lernen neu gestalten)
Die soziale Ungleichheit im Hochschulsystem nimmt nur sehr langsam ab. Als eine Begründung gilt die Ausrichtung von Hochschulen an einem akademischen Habitus, der andere Habitus ausgrenzt und zu Passungsproblematiken führt. Wie diese Passungsproblematiken aufseiten der Studierenden entstehen ist ein mittlerweile unter suchtes Phänomen. Die Lehrenden und ihre Praktiken als zentraler Part der Lehr-Lern-Interaktion werden kaum betrachtet. Dieser Beitrag zeigt anhand einer Sekundärauswertung von zehn qualitativen Studien Praktiken des Lehrhandelns und der Interaktion zwischen Lehrenden und Studierenden auf. Analysiert wurden die Studien im Hinblick auf die Frage wie doing difference stattfindet, also wie durch Lehrpraktiken Studierende kategorisiert werden und welche Selektions- und Ausgrenzungsprozesse dadurch stattfinden. Dabei stütze ich mich auf die abgedruckten Interviewpassagen ebenso wie auf die von den Autorinnen und Autoren gemachten Analysen. Die Lehrpraktiken zeichnen sich durch eine geringe Diversitätssensibilität mit wenig Hilfsangeboten und eine starke Befürwortung von Leistungsorientierung und Selektion aus.
Keywords: Lehrpraktiken; Lehrhabitus; Fachhabitus : Selektion; Sozialisation

Professionalisierungsmöglichkeiten angehender Lehrkräfte in Praxisphasen - Rodemer, Marc; Mientus, Lukas; Wiedmann, Julia; Nowak, Anna; Pollmeier, Pascal (Frühe naturwissenschaftliche Bildung)

Entanglement-assisted quantum speedup: Beating local quantum speed limits - Yasmin, Farha; Sperling, Jan (Physical Review A)

Study on hydrodynamic and mass transfer performance of Mellapak 250Y for FPSO units exposed to permanent tilt and roll motion - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Holger, Kryk; Ehlert, Thomas; Kenig, Eugeny Y.; Hampel, Uwe